Microhistory of a Microscopic Society: An Approximation to the Jesuit Mission of the Upper Napo (Ecuador), 1870-1896 - Moreno Tejada, Jaime (Revista Complutense de Historia de América, 2012)
This study represents a re-evaluation of the Jesuit experience in the Upper Napo of Ecuador at the turn of the twentieth century. The article is a micro-historical approach to the links that existed between Jesuits, Indians, merchants and civil authorities, in a time of great transformations –both in Ecuador and in the Amazon. This research is based on primary sources, published as well as archival, many of which have not been studied to this day.